Development of Differentiated E-Learning to Improve Students' Motivation and Learning Independence at SMAN 1 Panggang, Gunungkidul Regency - Ari Mardian; Herman Dwi Surjono (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to: (1) develop differentiated e-learning media tailored for SMAN 1 Panggang, Gunungkidul; (2) evaluate the feasibility of the media based on expert validation; (3) assess its practicality for students and teachers; and (4) determine its effectiveness in improving student motivation and learning independence. The research employed the Alessi & Trollip development model, which consists of three stages: planning, design, and development. The initial trial involved three diverse Phase F students, while the product testing was conducted on two classes: a control group and an experimental group, each comprising 36 Phase F students. Data collection included interviews, questionnaires, and validation assessments from material and media experts. Data analysis methods included N-Gain calculations, independent sample t-tests, and paired t-tests. The results of this research and development are as follows: (1) development of a Moodle-based differentiated e-learning platform accessible via www.esman1panggang.com, featuring programming algorithm materials adapted to students' diverse learning styles across four sessions; (2) validation by material experts (4.11) and media experts (4.10), both categorized as